2022
DOI: 10.3389/fbioe.2022.1008664
|View full text |Cite
|
Sign up to set email alerts
|

The hybrid crosslinking method improved the stability and anti-calcification properties of the bioprosthetic heart valves

Abstract: The bioprosthetic heart valves (BHVs) are the best option for the treatment of valvular heart disease. Glutaraldehyde (Glut) is commonly used as the golden standard reagent for the crosslinking of BHVs. However, the obvious defects of Glut, including residual aldehyde toxicity, degradation and calcification, increase the probability of valve failure in vivo and motivated the exploration of alternatives. Thus, the aim of this study is to develop a non-glutaraldehyde hybrid cross-linking method composed of Neomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have also demonstrated that the loss of HA in tissues is linearly correlated with calcification ( Johansson et al, 2011 ). Our previous study showed that the GAG content in pericardial tissue was only 2%–4% in pericardial tissue, which is far lower than that in valve tissue ( Song et al, 2021 ; Liu et al, 2022 ). Therefore, increasing the HA content in pericardial tissues might enhance the anticalcification properties of BHVs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies have also demonstrated that the loss of HA in tissues is linearly correlated with calcification ( Johansson et al, 2011 ). Our previous study showed that the GAG content in pericardial tissue was only 2%–4% in pericardial tissue, which is far lower than that in valve tissue ( Song et al, 2021 ; Liu et al, 2022 ). Therefore, increasing the HA content in pericardial tissues might enhance the anticalcification properties of BHVs.…”
Section: Discussionmentioning
confidence: 88%
“…However, several drawbacks, such as residual free aldehydes, cytotoxicity, poor biocompatibility, and calcification, are frequently encountered with Glut-crosslinked BHVs ( Liu et al, 2019 ). Although many studies are exploring new crosslinking reagents or methods to replace Glut, none of them have been applied in the clinic ( Tam et al, 2015 ; Hu et al, 2021 ; Liu et al, 2022 ). Neutralizing the free aldehyde groups in Glut-fixed BHVs can enhance tissue durability, reduce calcification potential, and even stimulate partial endothelialization ( Gulbins et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation